Periodontal associations in cardiovascular diseases: The latest evidence and understanding - C.M. Nguyen; J.W.M. Kim; V.H. Quan; B.H. Nguyen; S.D. Tran (Elsevier, 2015)
Periodontal and cardiovascular diseases (CVD) are inflammatory diseases. Recent epidemiological studies have associated the effect of periodontitis on CVD progression. Findings of oral pathogens in carotid atheromas provided a plausible relationship between these two diseases. One possible mechanism is the infiltration of oral/periodontal pathogens through inflamed and ulcerated gingival epithelium. This results in translocation of oral pathogens throughout the systemic circulation affecting vascular tissues, and initiating a cascade of inflammatory reactions detrimental to the cardiovascular system. In addition, leakage of pro-inflammatory cytokines/chemokines from the ulcerated periodontium into the bloodstream may cause the production of hepatic acute-phase proteins. Moreover, as chronic bacteremia occurs, the adaptive immune system is activated. Antibodies produced in response to periodontal pathogens trigger a cross-reaction between endothelial cells and modified low-density lipoprotein to enhance the movement of lipids into cells within the vessel wall. Some antibodies and inflammatory cytokines promote the Th1 response, thereby further activating macrophages within the atheroma. These plausible mechanisms are contributing factors in initiating and propagating atherogenesis. This review discusses the current understanding of CVD pathology/periodontitis, potential underlying mechanisms regarding this association, and general guidelines for treating patients with CVD risks.